Cannabidiol and palmitoylethanolamide are anti-inflammatory in the acutely inflamed human colon - Couch, Daniel G.; Tasker, Chris; Theophilidou, Elena; Lund, Jonathan N.; O'Sullivan, Saoirse (Portland Press, 2017)
Objective: We sought to quantify the anti-inflammatory effects of two cannabinoid drugs, cannabidiol (CBD) and palmitoylethanolamide (PEA), in cultured cell lines and compared this effect with experimentally inflamed explant human colonic tissue. These effects were explored in acutely and chronically inflamed colon, using inflammatory bowel disease and appendicitis explants.